Agronomic and Phytochemical Characterization of Chickpea Local Genetic Resources for the Agroecological Transition and Sustainable Food Systems - Lara Abou Chehade; Silvia Tavarini; Maria Francesca Bozzini; Gilbert Koskey; Lisa Caturegli; Daniele Antichi; Luciana G. Angelini (Agronomy, 2024)
Legume crops play a key role in hastening both the agroecological and protein transition and improving the sustainability of cropping systems. Among legumes, chickpea (Cicer arietinum L.) is a valuable source of protein, fibers, and nutraceutical compounds, providing important agri-environmental effects. Nevertheless, few studies have explored the effect of genetic characteristics on production and quality traits in chickpea. Chickpea landraces seem particularly interesting for their positive agronomic and quality characteristics, opening the door for innovation in sustainable food systems. Thus, the present study aimed to characterize two chickpea Tuscan landraces (Rugoso della Maremma and Cappuccio della Valtiberina) in comparison with widely distributed commercial chickpea varieties (Ares, Maragià, Pascià, Principe, Reale, Sultano, and Vittoria). Our findings highlighted positive agronomic traits of landraces in terms of seed yield and yield components, demonstrating performance that is either superior or comparable to commercial varieties. Notably, Cappuccio della Valtiberina showed the highest 1000-seed weight (425.50 g), followed by Maragià (432.92 g), Principe (392.32 g), and Reale (382.79 g), and the highest harvest index (0.55), similar to Reale (0.55). Overall, landraces achieved 18.75% higher yields than commercial varieties. Regarding chickpea quality, landraces exhibited profiles comparable to those of commercial genotypes in terms of protein and oil content, as well as nutraceuticals. Interestingly, the two landraces had the most favorable ω-6/ω-3 ratios (Cappuccio della Valtiberina, 12.45; Rugoso della Maremma, 13.71) among the genotypes except for Maragià (11.78), indicating better nutritional quality compared to commercial varieties (>14.00). These results demonstrated that landraces could offer promising prospects for future chickpea breeding programs, aiding in the selection of genotypes capable of adapting to changing growing conditions and supporting the development of sustainable food systems.